An Interfacial Nanospike‐Structured Cathode for Low Temperature Solid Oxide Fuel Cells. Issue 9 (14th October 2014) - Ding, Hanping; Xue, Xingjian
<x xml:space="preserve">Abstract</x> A nanospike structured cathode is fabricated by combining a discharge treatment with a low‐temperature sintering process. The fuel cell with a nanospike‐structured cathode exhibits superior electrochemical performance at low operating temperatures (350–550 °C) and demonstrates certain thermal‐cycling stability. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>